Pengaruh Penambahan Bungkil Kedelai terhadap Konsumsi Pakan, Pertambahan Bobot Badan Harian, dan Konversi Pakan pada Sapi Peranakan Simmental - Rico; Novi Eka Wati; Adisti Rastosari (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
The objective of the researh was to study the effect of additions soybean meal in ration on the feed consumption, daily weight gain and feed convertion in Simmental cattle. The experiment used eight male Simmental cattle around 2 years old with an average weight of 198,65 Â± 14,57 kilograms. The cattle kept for 35 days and given rations P0 (rations ranchers) and P1 (rations plus soybean meal). Data was obtained, then analyzed using independent sample t-test assisted with SPSS version 17.00 software. The result showed that the addition of soybean meal did not affect on dry matter consumption, daily weight gain, and feed convertion but, the crude protein consumption was increased. Keywords: dry matter consumption, daily weight gain, feed convertion